Lung cancer survival in Germany: A population-based analysis of 132, 612 lung cancer patients. Issue 3 (December 2015) - Eberle, Andrea; Jansen, Lina; Castro, Felipe; Krilaviciute, Agne; Luttmann, Sabine; Emrich, Katharina; Holleczek, Bernd; Nennecke, Alice; Katalinic, Alexander; Brenner, Hermann
Highlights: This study delivers up-to-date estimates of lung cancer survival in Germany. Survival differed markedly according to age, histological group and stage at diagnosis. Women showed higher survival rates than men independent of age, histology and stage. Abstract: Objectives: Lung cancer is the most common cancer-related death worldwide. In Germany it accounts for 25% of cancer deaths in men, and 14% in women. The aim of this study is to provide an overview of 5-year relative survival by sex, age, histology, and tumour stage in Germany representing a population of 26.7 million people. Materials and methods: The study is based on a pooled German dataset including data from 12 population-based cancer registries covering around one third of the German population. A total of 132, 612 patients diagnosed with lung cancer from 2002 to 2010 were included in the analysis. Survival estimates for the time period 2007–2010 were calculated using period analysis. Differences in survival between sexes were tested for statistical significance by model-based period analysis (poisson regression model). The relative excess risk (RER) of death (women vs. men) was extracted from the model with the p value for the difference in RER. Results: The overall age adjusted 5-year relative survival was 15.5% (standard error (SE) 0.2) for men and 20.3% (SE 0.3) in women. Survival differed markedly according to age (men: <60 years 18.5% vs. 80+ years 8.4% and women 23.7% vs. 10.6%, respectively), histology (largest difference between histological groups: men 25.7 and women 44.4% points) and stage (men: UICC Ia 62.9%, vs. UICC IV 4.6% and women 75.2% vs. 7.0%, respectively). Our study showed survival advantages for women compared to men, most notably in younger aged patients (RER 0.83, p < 0.0001), patients with adenocarcinoma (RER 0.80, p < 0.0001), and patients with lower stage cancer (RER 0.62, p < 0.0001). Conclusions: This study presents up-to-date survival estimates for lung cancer in Germany. Compared to other European countries survival was relatively high. Women showed higher survival than men independent of age, histology and stage. The reasons for the survival differences require further clarification.